ENGLISH MASTERY OF STUDENTS OF ENGINEERING FACULTY SRWIJAYA UNIVERSITY ACADEMIC YEAR 2010/2011 - Sofendi - - (Politeknik Negeri Sriwijaya, 2011)
This study aims at finding out English mastery of students of Engineering Faculty Sriwijaya University academic year 2010/2011. Research instrument was in the form of test given to 518 students. The result shows that the majority of students (79.52% or 412 students) still have a problem to get the minimum score of TOEFL-like test as required by Engineering Faculty Sriwijaya University. The students’ English mastery is relatively problematic if they just learn English based on the curriculum or if they do not learn English at all during their formal lectures. This problem can be overcome if the students learn English independently during their lectures. TOEFL-llike test scores required by Engineering Faculty Sriwijaya University still needs to be improved in order ro achieve the demand of Sriwijaya University as a world class university in the future.